An Estimate on Riemannian Manifolds of Dimension 4 (Analysis in Theory and Applications, 2016)
We give an estimate of type $ \sup × \inf $ on Riemannian manifold of dimension 4 for a Yamabe type equation.
Keywords: $ \sup × \inf $; Riemannian manifold; dimension 4.